Pragmatic (Im)politeness in the Language of Political Advertisements in Selected Nigerian Newspapers (British Journal of Multidisciplinary and Advanced Studies, 2025)
Language is central to politics because it is the instrument through which politicians exercise authority and influence the people. While evidence abounds on numerous scholarly efforts to unravel the hidden meaning in varieties of political discourse, it can be observed that very little has been done on the pattern of impoliteness employed in political communication especially, political advertisements. Unlike previous studies that have examined political discourse from the angle of interviews and speeches, this study examines (im)politeness as a meaning-making tool employed by politicians in political advertisements. The study employs Leech’s (1983) politeness model to drive its analysis. Thirty political advertisements were published by the selected newspapers during the covered by the study. The study seeks to establish the extent of conformity to general communicative principles in political advertisement. Findings show that the competitive nature of elections is shown in the- language of political advertisements and that politicians use them to achieve two objectives: solicit for votes and blackmail their opponents, albeit indirectly because of the need for polite communication. Even though the adverts contain a blend of polite and impolite communication, the impoliteness is masked. In essence, the notion of politeness as a tool for maintaining social cohesion does not apply to political advertisements.